The University Elementary School a descriptive analysis - Matanguihan, Lourdes Lescano 1944- ([Quezon City s.n.], 1973)
This study describes the school's total operation, functions, organizational structure, instructional program, characteristics of the student population, the teaching staff, and problems. The school has functioned as a service school for children of University personnel (while admitting also other children) and a laboratory school for some units of the university and other educational institutions. It was administered from April 19, 1969 to January 31, 1973 by the Office of the President through the Vice-President for Academic Affairs from where it was returned on February 1, 1973 to the College of Education. Its curriculum is subject to faculty revision.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Philippines. University. Elementary School